2017
DOI: 10.1002/tesq.375
|View full text |Cite
|
Sign up to set email alerts
|

Preservice Teachers’ Developing Conceptions of Teaching English Learners

Abstract: In this study, 12 preservice teachers in a community college English as a second language (ESL) K-12 teacher education program drew pictures and wrote descriptions of teachers teaching English language learners (ELLs) at the beginning and end of an ESL methods course. Using content analysis, the researcher analyzed the drawings and descriptions with respect to the role of the teacher, the role of the students, the teaching strategies shown, the instructional content, and how the drawings changed over the semes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 30 publications
1
30
0
1
Order By: Relevance
“…This study contributes to the current literature by describing a range of conceptions of teaching that may empower or limit teachers’ use of virtual reality (VR) technology for the teaching of composition writing. Knowledge of teachers’ conceptions may also provide useful insight for teacher educators and policymakers to enhance educational practices ( Kelly and Beth, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…This study contributes to the current literature by describing a range of conceptions of teaching that may empower or limit teachers’ use of virtual reality (VR) technology for the teaching of composition writing. Knowledge of teachers’ conceptions may also provide useful insight for teacher educators and policymakers to enhance educational practices ( Kelly and Beth, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Internal tensions are those dissonances we encounter between who we are in this moment and who we would like to become; in other words, performed identities versus imagined identities (Kelly, 2018). These types of tensions might include, among others, conceptual versus procedural knowledge (Kanno & Stuart, 2011), theory and/or discourse versus practice (Kanno & Stuart, 2011;Song, 2016), who we believe we are versus who we "really" are, and even tensions arising as multiple identities compete within the teacher, such as marginalization versus privilege (Varghese et al, 2016).…”
Section: A Word About Tensionsmentioning
confidence: 99%
“…We know, for example, that teacher beliefs are integral to the formation of a teacher’s concept of the ideal LTI. However, Kelly (2018) found that teacher beliefs may not change very much in LTE programs—even such deficit views of learners as passive and teachers as deliverers of information—unless such change becomes an explicit focus of the teacher educator.…”
Section: Language Teacher Identity and Lti Developmentmentioning
confidence: 99%
See 2 more Smart Citations